P274 Designing a Behavioural-Educational Intervention Using Intervention Mapping to Reduce the High Rates of Paediatric Asthma Hospital Admissions in an Inner-City Area of Birmingham. (19th November 2012) - Ikram-Bashir, F; Barrett, L; Cummins, C; Pattison, H
Abstract : Background: Interventions based on empirically supported theory are effective in eliciting behaviour change (BC) (Michie & Prestwich, 2010). We used intervention mapping to design a BC intervention to promote effective asthma management. Method: An evidence review on BC interventions for asthma was conducted; quantitative admissions data was collated; and qualitative research was used to explore family and patient experiences. These were used in the six processes of intervention mapping: needs assessment, proximal programme objective matrices, theory-based methods and practical strategies, intervention design, adoption and implementation, and evaluation. Findings: The six stages demonstrated that self-management behaviours are a critical component of asthma care and that childhood asthma care may be influenced through behaviour and environment. The process showed how intervention methods based on self-regulatory theory (Leventhal et al., 1984) are applicable to self-management behaviours and can be translated into practical applications for asthma self-management. Figure 1 . Intervention mapping process diagram (Bartholomew et al., 2001) Step one involved conducting a literature review, collecting preliminary data and developing the asthma PRECEDE model. Step 2 highlighted the at-risk group and explores relevant theories/frameworks e.g. Asthma self-management behavioural framework (Bartholomew et al., 2001). Performance objectives and determinants were established in order to devise a change objective matrix. Step 3 linked BC techniques to determinants and change objectives in order to change behaviour. Step 4 was the intervention design targeting asthma self-management. Key features were child centred teaching including a video and facilitating family/GP links. Step 5 encompassed the logistics of the intervention i.e. mode of delivery, costing and outcome expectations e.g. perceived benefits and better health. Step 6 outlined how the intervention would be evaluated including baseline and follow-ups, review of ED attendances, self-reported measures, Asthma Quality of Life Scale and Paediatric Asthma Control Test. Discussion: The intervention mapping process aided the design of an intervention tailored to a child's own data and to the specific needs of a child/family. The intervention should help a child progress to more advanced asthma management and promote a tie between child/family and GP . The next step is to implement and evaluate this intervention at Birmingham Children's Hospital to tackle the paediatric high rates of asthma hospital admissions. Words: 345 (excluding subheadings and diagram)